2010
DOI: 10.1111/j.1749-6632.2010.05613.x
|View full text |Cite
|
Sign up to set email alerts
|

RelB regulates manganese superoxide dismutase gene and resistance to ionizing radiation of prostate cancer cells

Abstract: Radiation therapy is in the front line for treatment of localized prostate cancer. However, a significant percentage of patients have radiation-resistant disease. The NF-κB pathway is an important factor for radiation resistance, and the classical (canonical) pathway is thought to confer protection of prostate cancer cells from ionizing radiation. Recently, the alternative (non-canonical) pathway, which is involved in prostate cancer aggressiveness, has also been shown to be important for radiation resistance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(55 citation statements)
references
References 72 publications
2
52
0
1
Order By: Relevance
“…NF-κB has been linked to cell proliferation, invasion, angiogenesis, metastasis, suppression of apoptosis and chemoresistance in multiple tumors (38,39). In addition, evidence suggests that NF-κB is significant in the growth and radio/chemoresistance of prostate cancer (40)(41)(42)(43)(44). Curcumin is able to suppress NF-κB activation by an Akt-dependent or Akt-independent inhibition of IKK (15,16,45).…”
Section: Discussionmentioning
confidence: 99%
“…NF-κB has been linked to cell proliferation, invasion, angiogenesis, metastasis, suppression of apoptosis and chemoresistance in multiple tumors (38,39). In addition, evidence suggests that NF-κB is significant in the growth and radio/chemoresistance of prostate cancer (40)(41)(42)(43)(44). Curcumin is able to suppress NF-κB activation by an Akt-dependent or Akt-independent inhibition of IKK (15,16,45).…”
Section: Discussionmentioning
confidence: 99%
“…Disruption of the ROS production/detoxification cycle, contributes to the development of human pathologies, including age-related diseases, such as cancer (58,68,80,178), cardiovascular (38,139), neurodegenerative (178), and genetic disorders (33,88). ROS can also be generated by exogenous sources like ionizing radiation (IR) (75,110), through direct interactions with either cellular targets or with water, resulting in DNA damage and gene mutations (45,69) or cell death (110). However, under oxidative stress, ROS induces the intrinsic antioxidant enzymes to protect cells from ROS-induced toxicity (64).…”
Section: Oxidative Stress and Mpimentioning
confidence: 99%
“…Studies using mice (182) and fruit flies (40) demonstrated that MnSOD gene knockout is lethal; while MnSOD heterozygous mice with haplo-insufficiency can survive but are more susceptible to oxidative injury (169,171). The crucial role of MnSOD in protecting cells against oxidative stress has been extensively studied and thoroughly reviewed (75,89,123,130,150,161), pointing to the critical roles of MnSOD in maintaining cellular physiology in response to genotoxic conditions, such as oxidative stress. In addition to MnSOD gene transcription, accumulating evidence indicates that MnSOD enzymatic activity is enhanced via post-translational modifications.…”
mentioning
confidence: 99%
“…The most recent studies have shown increased levels of MnSOD expression in cancer cells of various tissue origins (Hu et al, 2005), positively correlating with aggressive or metastatic stages of cancers (Malafa et al, 2000;Ennen et al, 2011). Altered transcription factor profiles in cancer cells, such as aberrant activation of NFkB (Dhar et al, 2010;Holley et al, 2010), SP-1 (Dhar et al, 2010) and inactivation of p53 (Dhar et al, 2010), are suggested to be attributable to increases in MnSOD expression.…”
Section: /2mentioning
confidence: 99%